Long-term CD4 cell count recovery among Thai naive HIV-infected patients initiating HAART at low CD4 cell count - Chaiwarith R. (2014)
CD4 T cell recovery after highly active antiretroviral therapy (HAART) has been reported mostly from developed countries. A retrospective cohort study was conducted among naïve HN-infected patients initiating HAART between July 1, 2001 and December 31, 2004 at Chiang Mai University, Thailand. We evaluated the CD4 cell count recovery over 4 years among patients initiated HAART at low (CD4 count 51-200 cells/ mm3) and very low (CD4 count ≤ 50 cells/mm3)) CD4 counts. Of 287 patients, 153 and 134 had low and very low baseline CD4 count, respectively. There were 126 men (43.9%), and the mean age was 34.2 ± 7.9 years. The median baseline CD4 count was 50 cells/mm3 (IQR 25, 104). GPO-VIR®, (a combination of Iamivudine, stavudine, and nevirapine) was the most common prescribed HAART (262 patients, 91.3%). Overall, the mean CD4 count significantly increased 108 cells/mm3 in the first 6 months after HAART initiation and continued to increase up to 4 years, but in the lesser extent. The overall slope of CD4 count was not significantly different between groups. (p = 0.052) The median time to achieve CD4 count of ≥ 200 cells/mm3 was 6 and 18 months in those with low and very low baseline CD4 count, respectively (p<0.001). By 4 years, 19.9% of patients achieved CD4 count of > 500 cells/mm3. The earlier HAART is initiated among patients with low and very low baseline CD4 count, the sooner the patients will achieve adequate immune status to prevent morbidity and mortality from opportunistic infections. © 2009 Bentham Science Publishers Ltd.